Link and Match Analysis Of Vocational Education; Case Study Of Industrial Work Practice Students Of Class XI SMK Dharma Putra 1 Jakarta at PT. Bukaka Teknik Utama - Putri, Eka Kurnia (Al'Adzkiya Journal, 2021)
This study aims to find out how the implementation of internships at SMK Dharma Putra 1 Jakarta and whether a link and match has been created between what is done at school and what is done in partner institutions (industry). This research was conducted at SMK Dharma Putra 1 Jakarta and also PT. Unlock Main Techniques. This school was chosen because it is a place where researchers serve, while industry was chosen based on recommendations from schools because it is one of the industries that have collaborated with schools and has concern for the field of education. The method used in this research is a qualitative method with a case study approach. Data collection techniques used are interviews, observations, documentation studies and a combination of the three or triangulation. In this study, the data source was selected by purposive sampling which was selected based on the fulfillment of the criteria and was snowball sampling. The informants of this study were 23 people. In processing and analyzing data using the Miles and Huberman model, namely through data reduction, data display and conclusions. The validity of the data was tested through triangulation. The results of this study indicate that of the three existing skill competencies, accounting expertise competencies have not reached a great level of relevance, this can be proven by the results of interviews and documentation. The cause of this problem is due to several things, namely the difficulty of collaborating with industry, curriculum synchronization that is only limited to administration, and the lack of trust from industry to schools to be able to provide students with internships, as well as the less visible role of the government for this program.